The optimization of electric motorcycle batteries at battery swapping stations in Bangkok, Thailand: Comparing the performance between single and transshipment inventory management - Witoowithaya, Thongthida (2022)
Recently the ECO trends have begun across the world which may lead to being an advantage for Thailand in evolving from an internal combustion engine (ICE) manufacturer to an electric vehicle (EV) hub in Asia even though Hence, the new battery charging model has innovated, called the battery swapping. However, the demand for EVs in Thailand nowadays is not high enough to take the advantage of the economy of scale due to people being concerned about the traveling distance per charging, the charging time length, the EV price, and the number of charging stations may not have enough. In this study, we will explore inventory management to find the most suitable management between single and transshipment inventory management in managing BSS under inventory policies of (S-1, S) with the Poisson distribution, investigated by the Arena Simulation Program. Also, investigate the 3 possible scenarios of opportunities and challenges for the Thai automotive manufacturing supply chain: (1) increased number of stocks; (2) Decreased charging time; (3) Increased number of stocks and decrease charging time. The result shows that the transshipment BSS has significantly outstanding performance in responding to the system due to the support from other BSS when more than enough inventory occurs, sharing happens.